علامہ عبدالباقی بن قانعؒ کی حیات و علمی خدمات: The Life and Scholarly Contributions of Allāmah ʿAbd al-Bāqī ibn Qāni - Dr. Hafiz Saeed ur Rehman, (Al Manhal Research Journal, 2025)
This research article provides a comprehensive scholarly analysis of the life, intellectual contributions, and traditionary status of Allama Abdul Baqi ibn Qani’ al-Baghdadi (d. 351 AH), a prominent Muhaddith, jurist, and historian of the Abbasid era. Born in Baghdad in 265 AH, Ibn Qani’ was raised in a family of profound learning and embarked on extensive academic journeys across major Islamic scientific centers, including Kufa, Basra, and Wāsiṭ, to seek Prophetic traditions. Renowned as a prolific traveler and an expert in Hadith (Wasi’ al-Rihlah), his scholarship attracted distinguished students such as Al-Daraqutni and Al-Jassas. The study critically examines his literary legacy, specifically focusing on his seminal work, Mu’jam al-Sahaba, and addresses the scholarly debates regarding his reliability as a narrator. While certain critics noted a decline in his memory (Ikhtilat) during the final two years of his life, this paper argues, through a synthesis of historical evidence and biographical evaluations by Ibn Hajar and Al-Dhahabi, that his earlier narrations remain authoritative and widely accepted within the Hadith sciences. Ultimately, the research underscores Ibn Qani’s pivotal role in preserving Islamic heritage and vindicates his status as a trustworthy guardian of the prophetic tradition.